Retinal S-opsin dominance in Ansell's mole-rats (Fukomys anselli) is a consequence of naturally low serum thyroxine. - Mladěnková, Nella (Jihočeská univerzita, 2020)
Mammals usually possess a majority of medium-wavelength sensitive (M-) and a minority of short-wavelength sensitive (S-) opsins in the retina, enabling dichromatic vision. Unexpectedly, subterranean rodents from the genus Fukomys exhibit an S-opsin majority, which is exceptional among mammals, albeit with no apparent adaptive value. Because thyroid hormones (THs) are pivotal for M-opsin expression and metabolic rate regulation, we have, for the first time, manipulated TH levels in the Ansell's mole-rat (Fukomys anselli) using osmotic pumps. In Ansell's mole-rats, the TH thyroxine (T4) is naturally low, likely as an adaptation to the harsh subterranean ecological conditions by keeping resting metabolic rate (RMR) low. We measured gene expression levels in the eye, RMR, and body mass (BM) in TH-treated animals. T4 treatment increased both, S- and M-opsin expression, albeit M-opsin expression at a higher degree. However, this plasticity was only given in animals up to approximately 2.5 years. Mass-specific RMR was not affected following T4 treatment, although BM decreased. Furthermore, the T4 inactivation rate is naturally higher in F. anselli compared to laboratory rodents. This is the first experimental evidence that the S-opsin majority in Ansell's mole-rats is a side effect of low T4, which is downregulated to keep RMR low.
Retinal S-opsin dominance in Ansell's mole-rats (Fukomys anselli) is a consequence of naturally low serum thyroxine.
Keywords: subterranean rodents; RMR